2021
DOI: 10.1002/jemt.23752
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural studies of the pecten oculi of the Garganey (Anas querquedula, Linnaeus 1758) and the Eurasian common moorhen (Gallinula chloropus chloropus, Linnaeus 1758)

Abstract: The present study represents the first attempts to give a full anatomical comparison of the vascular pigmented pectin oculi of the diurnal activity Anas querquedula and Gallinula chloropus chloropus. For achievement of this work, 10 mature birds from each species were examined under stereo‐ and electron microscope. The pecten oculi of A. querquedula is triangular fan‐like, while in Gallinula c. thin like‐fold. In both examined birds, the pecten oculi located postero‐anteriorly intraocular just adjacent to opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 29 publications
6
12
0
Order By: Relevance
“…Additionally, the pecteneal apex differs slightly between different species of birds. In this study, the free pecteneal apex was fused with one another, forming a free apical bridge that was directed towards the gelatinous vitreous body and ciliary body, similar to what was seen in a variety of diurnal birds, such as the migratory Garganey, budgerigar, black kite, chicken, white stork, Baladi ducks, common buzzard, seagulls, northern bald ibis, and migratory European wild quail (Abumandour et al, 2021;Abumandour et al, 2022;Alan et al, 2020;Gültiken et al, 2012;Ince et al, 2017;Kiama et al, 1994;Micali et al, 2012;Moselhy & El-Hady, 2019;Onuk, Tutuncu, et al, 2013;Puzzolo et al, 1985;Yilmaz et al, 2021), while the free pecteneal apex…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…Additionally, the pecteneal apex differs slightly between different species of birds. In this study, the free pecteneal apex was fused with one another, forming a free apical bridge that was directed towards the gelatinous vitreous body and ciliary body, similar to what was seen in a variety of diurnal birds, such as the migratory Garganey, budgerigar, black kite, chicken, white stork, Baladi ducks, common buzzard, seagulls, northern bald ibis, and migratory European wild quail (Abumandour et al, 2021;Abumandour et al, 2022;Alan et al, 2020;Gültiken et al, 2012;Ince et al, 2017;Kiama et al, 1994;Micali et al, 2012;Moselhy & El-Hady, 2019;Onuk, Tutuncu, et al, 2013;Puzzolo et al, 1985;Yilmaz et al, 2021), while the free pecteneal apex…”
Section: Discussionsupporting
confidence: 73%
“…These coiled surfaces provide a large surface area for efficient nutrient exchange between the blood capillaries and the retina; additionally, this specialized structure helps to maintain the health and functionality of the non-vascular retina by ensuring a constant supply of nutrients. Moreover, high SEM magnification showed that the pecteneal pleat's outer surface is covered by a thin smooth vitreopecteneal limiting membrane separating the pleat's outer surface from the gelatinous vitreous body, similar to that observed in many avian species (Abumandour et al, 2021;Abumandour et al, 2022;Elghoul et al, 2022;Kandyle et al, 2022;Uehara et al, 1996).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations